Resin mixture for 3D printing molding, material for 3D printing molding, molded article, and molding method

By using the mixture of the substrate resin and the organic cross -linked hollow particles in the 3D printing modeling technology, it solves the problem of being difficult to make full use of the light quality effect of the hollow granules in existing technologies, and realizes the high modeling and lightweight 3D printing shape. Material.

CN119365324APending Publication Date: 2025-01-24ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046480.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-20
Filing Date
2023-06-02
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing 3D printing modeling technology is difficult to fully utilize the lightweight effect of hollow particles.

Method used

A resin mixture for 3D printing modeling containing matrix resin and organic cross-linked hollow particles is used. By adding organic cross-linked hollow particles to the matrix resin, the lightweight and styling properties of the molded object are improved.

Benefits of technology

The excellent modeling and lightweight effect of 3D printing modeling materials can form a complex three -dimensional shape with sufficient strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365324A_ABST
    Figure CN119365324A_ABST
Patent Text Reader

Abstract

The present invention provides a resin mixture for 3D printing molding, the resin mixture for 3D printing molding being capable of forming a material for 3D printing molding, the material for 3D printing molding having excellent moldability and being capable of forming a lightweight molded article. The invention provides a resin mixture for 3D printing modeling. The resin mixture contains matrix resin and organic cross-linked hollow particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a resin mixture for 3D printing modeling, a material for 3D printing modeling, a modeling object and a modeling method. Background Art

[0002] In recent years, 3D printing technology (three-dimensional modeling technology) has attracted attention as a method for manufacturing resin molded bodies. In 3D printing technology, the degree of design freedom is high, various molded objects with complex three-dimensional shapes can be manufactured, and the design time and cost can be reduced, so it is gradually being used in a wide range of applications.

[0003] For example, most components of mobile bodies such as drones have complex three-dimensional shapes, and are sometimes manufactured using 3D printing technology. When manufacturing such components, 3D printing materials are required to have excellent modeling properties (i.e., they can reproduce complex three-dimensional shapes and produce a model with sufficient strength). On the other hand, mobile bodies such as drones are also required to have improved driving time and lightweight components.

[0004] For example, Patent Document 1 describes a method for manufacturing a three-dimensional object, which is characterized in that it includes: a layer forming step, forming a layer using a three-dimensional modeling composition; and a binder liquid providing step, providing a binder liquid containing a binder to a specified area in the above-mentioned layer. The method for manufacturing the above-mentioned three-dimensional object is a method for manufacturing a three-dimensional object by repeating these steps in sequence. The above-mentioned three-dimensional object is composed of a material containing hollow particles, and the above-mentioned hollow particles have a first region and a second region surrounded by the first region as a hollow portion. The difference n1-n2 between the refractive index n1 of the structural material of the above-mentioned first region and the refractive index n2 of the structural material of the above-mentioned second region is greater than 0.25.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-010914. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, the inventors conducted in-depth research and found that in Patent Document 1, although the three-dimensional modeling object is composed of a material containing hollow particles, and the above-mentioned hollow particles have a first region and a second region as a hollow portion surrounded by the first region, there is a problem that the lightweight effect brought about by the use of hollow particles cannot be exerted through the 3D printing modeling method.

[0010] The object of the present invention is to provide a resin mixture for 3D printing modeling, wherein the resin mixture for 3D printing modeling can form a 3D printing modeling material, and the 3D printing modeling material has excellent modeling properties and can form a lightweight modeling object.

[0011] Solutions for solving problems

[0012] The present inventors have conducted studies to achieve the above object and have found that the above object can be achieved by using organic crosslinked hollow particles as hollow particles in addition to a matrix resin, thereby completing the present invention.

[0013] That is, according to the present invention, the following resin mixture for 3D printing is provided.

[0014] [1] A resin mixture for 3D printing, comprising a matrix resin and organic cross-linked hollow particles.

[0015] [2] The resin mixture for 3D printing according to [1], wherein the apparent density of the organic cross-linked hollow particles is 0.2 to 0.9 g / cm 3 .

[0016] [3] The resin mixture for 3D printing according to [1] or [2], wherein the content of the organic crosslinked hollow particles is 1 to 70 parts by weight relative to 100 parts by weight of the total content of the matrix resin and the organic crosslinked hollow particles.

[0017] [4] The resin mixture for 3D printing according to any one of [1] to [3], wherein the organic crosslinked hollow particles have a shell formed of a shell polymer containing a crosslinkable monomer unit.

[0018] [5] The resin mixture for 3D printing according to any one of [1] to [4], wherein the shell polymer contains a heteroatom-containing crosslinkable monomer unit as the crosslinkable monomer unit.

[0019] Furthermore, according to the present invention, the following 3D printing modeling materials, modeling objects, and modeling methods are provided.

[0020] [6] A material for 3D printing modeling, which is formed from the resin mixture for 3D printing modeling described in any one of [1] to [5].

[0021] [7] The 3D printing modeling material according to [6], wherein the 3D printing modeling material is used for 3D printing modeling using a fused deposition modeling method.

[0022] [8] The 3D printing modeling material according to [6] or [7], wherein the 3D printing modeling material is in the shape of a filament.

[0023] [9] A modeled object obtained by 3D printing using the 3D printing modeling material described in any one of [6] to [8].

[0024]

[10] The object according to [9], wherein the object is obtained by 3D printing using a fused deposition modeling method.

[0025]

[11] A modeling method, using the 3D printing modeling material described in any one of [6] to [8] to perform 3D printing modeling.

[0026]

[12] The modeling method according to

[11] , wherein 3D printing modeling is performed using a fused deposition modeling method.

[0027] Effects of the Invention

[0028] According to the present invention, a resin mixture for 3D printing modeling can be provided, and the resin mixture for 3D printing modeling can form a material for 3D printing modeling. The material for 3D printing modeling has excellent modeling properties and can form a lightweight modeling object. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a photograph of the appearance of the 3D Benchy-shaped object obtained in Example 1. DETAILED DESCRIPTION

[0030] <Resin mixture for 3D printing>

[0031] The resin mixture for 3D printing modeling of the present invention contains a matrix resin and organic cross-linked hollow particles.

[0032] [Base resin]

[0033] The resin mixture for 3D printing modeling of the present invention contains a matrix resin.

[0034] As a matrix resin, there is no particular limitation as long as it can be used for 3D printing modeling, and thermoplastic resins are generally used. Specific examples of matrix resins include: acrylonitrile-butadiene-styrene resin (ABS resin); acrylonitrile-styrene resin (AS resin); polylactic acid (PLA resin); polyolefin resins such as polypropylene and polyethylene; polyamide resins such as PA6, PA66, and PA12; polyimide resins such as polyimide, polyamide-imide, and polyetherimide; polycarbonate resins; polystyrene resins; fluorine resins such as polyvinylidene fluoride and polytetrafluoroethylene; polyester resins; acrylic resins; polyvinyl chloride resins; polyetherketoneketone; poly(meth)acrylate; polyphenylene ether; polyphenylene sulfide; polysiloxane resins, etc. These matrix resins can be used alone or in combination of two or more.

[0035] As the base resin, from the viewpoint of being easy to obtain a molded object with small heat shrinkage and excellent reproducibility of the molded model, acrylonitrile-butadiene-styrene resin (ABS resin) and polylactic acid (PLA resin) are preferred. In addition, from the viewpoint of being easy to obtain a molded object with smaller heat shrinkage and better reproducibility of the molded model, polylactic acid (PLA resin) is more preferred. On the other hand, from the viewpoint of having low density and being able to make the final molded object further lightweight, acrylonitrile-butadiene-styrene resin (ABS resin) is more preferred.

[0036] [Organic cross-linked hollow particles]

[0037] The resin mixture for 3D printing of the present invention contains organic cross-linked hollow particles in addition to the above-mentioned matrix resin. The organic cross-linked hollow particles used in the present invention have a shell formed of a shell polymer and a hollow part.

[0038] The shell polymer is a polymer having a three-dimensional crosslinked structure and used to form the shell of the organic crosslinked hollow particles.

[0039] The shell polymer preferably contains a crosslinkable monomer unit. The crosslinkable monomer forming the crosslinkable monomer unit is a monomer having two or more polymerizable functional groups and forming a crosslink bond in the resin through a polymerization reaction. As the crosslinkable monomer, a compound having at least one ethylenically unsaturated bond as a polymerizable functional group is generally used.

[0040] Examples of the crosslinkable monomer that forms the crosslinkable monomer unit include a crosslinkable hydrocarbon monomer and a heteroatom-containing crosslinkable monomer.

[0041] The crosslinkable hydrocarbon monomer is not particularly limited, and examples thereof include divinylbenzene, divinylbiphenyl, divinylnaphthalene, dicyclopentadiene, ethylenetetracyclododecene and other difunctional crosslinkable hydrocarbon monomers, and divinylbenzene is particularly preferred. In addition, crosslinkable hydrocarbon monomers formed by polymers can also be used. Examples thereof include polybutadiene, polyisoprene, block copolymers of styrene and butadiene (SBS), block copolymers of styrene and isoprene (SIS), etc.

[0042] The heteroatom-containing crosslinking monomer is not particularly limited, and examples thereof include difunctional heteroatom-containing crosslinking monomers such as diallyl phthalate, allyl (meth)acrylate [the meaning of allyl acrylate and / or allyl methacrylate is the same hereinafter], ethylene glycol di(meth)acrylate, and pentaerythritol di(meth)acrylate; and trifunctional or higher heteroatom-containing crosslinking monomers such as trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol poly(meth)acrylate.

[0043] As heteroatom-containing crosslinking monomers, in addition to these, polyisocyanate compounds such as toluene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, tetramethylxylylene diisocyanate, isophorone diisocyanate (IPDI), hydrogenated toluene diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, meta-phenylene diisocyanate, biphenyl diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, and dimers or trimers thereof can be used. Furthermore, polyfunctional urethane (meth)acrylate compounds obtained by reacting a polyisocyanate compound with a hydroxyl-containing (meth)acrylate having a hydroxyl group and a (meth)acryloyl group can also be used. Specific examples of hydroxyl-containing (meth)acrylates include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane di(meth)acrylate, and dipentaerythritol penta(meth)acrylate; and isocyanuric acid di(meth)acrylate, and their ethylene oxide and caprolactone modified products.

[0044] As the heteroatom-containing crosslinking monomer, among these, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol poly(meth)acrylate and pentaerythritol tri(meth)acrylate are preferred, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate are more preferred, and ethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate and pentaerythritol tetramethacrylate are further preferred.

[0045] As the crosslinking monomer, a crosslinking hydrocarbon monomer, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol poly(meth)acrylate and pentaerythritol tri(meth)acrylate are preferred; divinylbenzene, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate are more preferred; and divinylbenzene, ethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate and pentaerythritol tetramethacrylate are further preferred.

[0046] The crosslinking monomers can be used alone or in combination of two or more. In the organic crosslinked hollow particles used in the present invention, the shell polymer preferably comprises a difunctional crosslinking monomer unit and a trifunctional or higher crosslinking monomer unit, more preferably a difunctional crosslinking monomer unit and a trifunctional or higher heteroatom-containing crosslinking monomer unit, and further preferably a difunctional crosslinking monomer unit and a trifunctional or higher heteroatom-containing crosslinking monomer unit. In addition, as a trifunctional or higher crosslinking monomer, there is no particular limitation, preferably a trifunctional to hexafunctional crosslinking monomer, more preferably a trifunctional to pentafunctional crosslinking monomer, and further preferably a trifunctional to tetrafunctional crosslinking monomer. In addition, in the organic crosslinked hollow particles used in the present invention, the shell polymer can also include a crosslinking hydrocarbon monomer unit and a heteroatom-containing crosslinking monomer unit.

[0047] The shell polymer may be substantially composed of only crosslinkable monomer units, or may contain monofunctional monomer units in addition to the crosslinkable monomer units.

[0048] The monofunctional monomer forming the monofunctional monomer unit is a monomer having only one polymerizable functional group, and a compound having an ethylenically unsaturated bond as the polymerizable functional group is generally used. Examples of the monofunctional monomer forming the monofunctional monomer unit include monofunctional hydrocarbon monomers and heteroatom-containing monofunctional monomers.

[0049] The monofunctional hydrocarbon monomer is not particularly limited, and examples thereof include aromatic vinyl monomers such as styrene, ethylvinylbenzene, vinyltoluene, α-methylstyrene, p-methylstyrene, and halogenated styrene; monoolefin monomers such as ethylene, propylene, butene, and 4-methyl-1-pentene; and diene monomers such as butadiene and isoprene. Among these, styrene and ethylvinylbenzene are preferred.

[0050] The heteroatom-containing monofunctional monomer is not particularly limited, and examples thereof include: hydrophilic monofunctional monomers; acrylic monovinyl monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and glycidyl (meth)acrylate; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated vinyl monomers such as vinyl chloride; dihalogenated vinyl monomers such as vinylidene chloride; vinyl pyridine monomers; urethane (meth)acrylate, allyl glycidyl ether, etc.

[0051] The hydrophilic monofunctional monomer preferably has a solubility of 1% by mass or more in water. The hydrophilic monofunctional monomer is not particularly limited, and examples thereof include monofunctional monomers having a hydrophilic group such as an acidic group-containing monomer, a hydroxyl group-containing monomer, an amide group-containing monomer, and a polyoxyethylene group-containing monomer.

[0052] Acidic group-containing monomers refer to monomers containing acidic groups. The acidic groups referred to here also include any of proton-donating groups (Bronsted acidic groups) and electron pair accepting groups (Lewis acidic groups). As acidic group-containing monomers, there are no particular limitations as long as they have acidic groups, and examples thereof include carboxyl-containing monomers and sulfonic acid-containing monomers. Examples of carboxyl-containing monomers include ethylenically unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butenetricarboxylic acid, and the like; monoalkyl esters of unsaturated dicarboxylic acids such as monoethyl itaconate, monobutyl fumarate, and monobutyl maleate, and the like. Examples of sulfonic acid-containing monomers include styrenesulfonic acid, and the like.

[0053] As a hydroxyl group-containing monomer, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc. are mentioned, for example.

[0054] Examples of the amide group-containing monomer include acrylamide and dimethylacrylamide.

[0055] Examples of the polyoxyethylene group-containing monomer include methoxypolyethylene glycol (meth)acrylate and the like.

[0056] The monofunctional monomer units can be used alone or in combination of two or more.

[0057] The content ratio of the cross-linkable monomer unit in the shell polymer is not particularly limited, and is preferably 20 to 100 mass%, more preferably 40 to 100 mass%, further preferably 60 to 100 mass%, and particularly preferably 80 to 100 mass%. By making the content ratio of the cross-linkable monomer within the above range, the shell will be densely covered with a covalent bond network, and the formation of interconnected pores and shell defects in the shell will be suppressed. As a result, the obtained 3D printing modeling material has excellent modeling properties and can form a lighter modeling object.

[0058] The content ratio of the monofunctional monomer unit in the shell polymer is not particularly limited, but is preferably 0 to 80% by mass, more preferably 0 to 60% by mass, further preferably 0 to 40% by mass, and particularly preferably 0 to 20% by mass.

[0059] The shell polymer may contain a heteroatom-containing monomer unit. As the heteroatom-containing monomer forming the heteroatom-containing monomer unit, the above-mentioned heteroatom-containing crosslinking monomer and heteroatom-containing monofunctional monomer can be cited. The content ratio of the heteroatom-containing monomer unit in the shell polymer is not particularly limited, but is preferably 1 to 99% by mass, more preferably 5 to 95% by mass, and further preferably 10 to 90% by mass.

[0060] The shell polymer is not limited to the above-mentioned shell polymers as long as it has a three-dimensional crosslinked structure and can form the shell of the organic crosslinked hollow particles. The shell polymer can be, for example, a phenolic resin, a melamine resin, a urea resin, an unsaturated polyester resin, an epoxy resin, a polyurethane resin, a silicone resin, an alkyd resin, a thermosetting modified polyphenylene ether resin, a thermosetting polyimide resin, a benzophenone resin, a Oxazine-based resins, urea-formaldehyde-based resins, allyl-based resins, aniline-based resins, maleimide-based resins, bismaleimide-triazine-based resins, liquid crystalline polyester-based resins, vinyl ester-based resins, unsaturated polyester-based resins, cyanate-based resins, polyetherimide resins, etc.

[0061] The organic crosslinked hollow particles used in the present invention are particles having a shell (shell) containing the above-mentioned shell polymer and a hollow portion surrounded by the shell. In the present invention, the hollow portion is a hollow space clearly distinguished from the shell of the organic crosslinked hollow particles formed by the resin. The organic crosslinked hollow particles used in the present invention can have one or more hollow portions, but in order to maintain a good balance between high porosity and mechanical strength, it is preferred to have only one hollow portion.

[0062] The organic crosslinked hollow particles used in the present invention generally have a shell without interconnecting pores and shell defects, and the hollow part is isolated from the outside of the particle by the shell, but the shell may have one or more interconnecting pores, and the hollow part is connected to the outside of the particle via the interconnecting pores. In addition, the shell of the organic crosslinked hollow particle and the barrier wall separating adjacent hollow parts in the case of having two or more hollow parts may be porous, in which case the hollow part has a size that can be clearly distinguished from a plurality of tiny spaces uniformly dispersed in the porous structure.

[0063] The hollow part of the organic crosslinked hollow particles used in the present invention may be filled with a gas such as air, or may contain a solvent.

[0064] The shape of the organic crosslinked hollow particles used in the present invention is not particularly limited as long as a hollow portion is formed inside. The outer shape of the organic crosslinked hollow particles is not particularly limited, but a spherical shape is preferred from the viewpoint of ease of production.

[0065] The external shape of the organic crosslinked hollow particles can be confirmed by, for example, observing the particles with SEM or TEM. In addition, the internal shape of the organic crosslinked hollow particles can be confirmed by, for example, observing a cross section of the particles with SEM or observing the particles with TEM.

[0066] The true density of the organic crosslinked hollow particles used in the present invention is not particularly limited, but is preferably 0.95 to 1.4 g / cm 3 , more preferably 1.0 to 1.3 g / cm 3 In addition, the true density of the organic crosslinked hollow particles refers to the density of only the shell portion of the organic crosslinked hollow particles. The true density of the organic crosslinked hollow particles can be adjusted by adjusting the monomer composition of the shell polymer.

[0067] The apparent density of the organic crosslinked hollow particles used in the present invention is preferably 0.2 to 0.9 g / cm 3 , more preferably 0.25 to 0.8 g / cm 3 From the viewpoint of obtaining a lighter shaped object, the apparent density of the organic crosslinked hollow particles is more preferably 0.25 to 0.7 g / cm 3 , particularly preferably 0.25 to 0.6 g / cm 3 , and most preferably 0.25 to 0.5 g / cm 3 On the other hand, from the viewpoint of further improving the molding properties of the obtained 3D printing molding material and improving the mechanical strength of the obtained molding, the apparent density of the organic cross-linked hollow particles is more preferably 0.3 to 0.8 g / cm 3 , particularly preferably 0.35 to 0.8 g / cm 3 , and most preferably 0.4 to 0.8 g / cm3 .

[0068] In addition, the apparent density of the organic crosslinked hollow particles refers to the density of the organic crosslinked hollow particles as a whole, including the shell part and the hollow part of the organic crosslinked hollow particles. The apparent density of the organic crosslinked hollow particles can be adjusted by adjusting the monomer composition of the shell polymer, the type and amount of the dispersion stabilizer and the hydrophobic organic solvent used when the organic crosslinked hollow particles are prepared by suspension polymerization, the suspension conditions, etc.

[0069] Specifically, the true density of the organic crosslinked hollow particles is measured by the following method. The organic crosslinked hollow particles are crushed in advance and then placed in a container having a volume of 100 cm 3 A volumetric flask is filled with about 10 g of fragments of organic cross-linked hollow particles, and the mass of the filled fragments is accurately weighed. Next, isopropanol is added to the volumetric flask in the same manner as the above-mentioned apparent density measurement, and the mass of isopropanol is accurately weighed. The true density (g / cm2) of the organic cross-linked hollow particles is calculated based on the following formula (I): 3 ).

[0070] True density of organic cross-linked hollow particles (g / cm 3 ) = [mass of the fragments of the organic cross-linked hollow particles] ÷ (100 - [mass of isopropanol] ÷ [density of isopropanol at the measurement temperature]) (I)

[0071] The apparent density D1 of the organic crosslinked hollow particles is measured as follows. First, a volume of 100 cm 3 Fill the volumetric flask to about 30 cm 3 The mass of the organic cross-linked hollow particles was accurately weighed. Next, the volumetric flask filled with the organic cross-linked hollow particles was accurately filled to the scale line with isopropanol while being careful not to mix in bubbles. The mass of isopropanol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm2) of the organic cross-linked hollow particles was calculated based on the following formula (II): 3 ).

[0072] The apparent density D1 (g / cm 3 ) = [mass of organic cross-linked hollow particles] ÷ (100 - [mass of isopropanol] ÷ [density of isopropanol at the measurement temperature]) (II)

[0073] The volume average particle size (Dv) of the organic crosslinked hollow particles used in the present invention is not particularly limited, and is preferably 1 to 50 μm, more preferably 1.5 to 40 μm, and further preferably 2 to 30 μm. In addition, the particle size distribution (Dv / Dn) (volume average particle size (Dv) / number average particle size (Dn) of the organic crosslinked hollow particles used in the present invention is not particularly limited, and is preferably 1.02 to 2.00, and more preferably 1.04 to 1.60.

[0074] The volume average particle size (Dv) and particle size distribution (Dv / Dn) of the organic crosslinked hollow particles can be adjusted by, for example, adjusting the monomer composition of the shell polymer, the type and amount of the dispersion stabilizer used when producing the organic crosslinked hollow particles by suspension polymerization, and the suspension conditions.

[0075] The volume average particle size (Dv) and number average particle size (Dn) of the organic crosslinked hollow particles can be measured by, for example, a laser diffraction particle size distribution measuring device, and the number average and volume average are calculated, respectively, and the obtained values ​​are used as the number average particle size (Dn) and volume average particle size (Dv) of the particles. The particle size distribution (Dv / Dn) is the value obtained by dividing the volume average particle size (Dv) by the number average particle size (Dn).

[0076] The thermal decomposition starting temperature of the organic cross-linked hollow particles used in the present invention is preferably 210 to 400°C, more preferably 220 to 350°C. By setting the thermal decomposition starting temperature in the above range, the modeling properties of the obtained 3D printing modeling material can be further improved, and the mechanical strength of the obtained modeling object can be improved. The thermal decomposition starting temperature of the organic cross-linked hollow particles is the temperature at which the weight is reduced by 5%. The thermal decomposition starting temperature of the organic cross-linked hollow particles can be measured by a TG-DTA device under air atmosphere at an air flow rate of 230 mL / min and a heating rate of 10°C / min.

[0077] The content of the organic cross-linked hollow particles is not particularly limited, and is preferably 1 to 70 parts by weight, more preferably 2 to 60 parts by weight, and further preferably 5 to 55 parts by weight, relative to a total of 100 parts by weight of the content of the matrix resin and the organic cross-linked hollow particles. In addition, from the viewpoint of being able to obtain a lighter modeling object, the content of the organic cross-linked hollow particles can be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more relative to a total of 100 parts by weight of the content of the matrix resin and the organic cross-linked hollow particles. On the other hand, from the viewpoint of being able to further improve the modeling properties of the obtained 3D printing modeling material and to improve the mechanical strength of the obtained modeling object, the content of the organic cross-linked hollow particles can be 50 parts by weight or less, 40 parts by weight or less, or 35 parts by weight or less relative to a total of 100 parts by weight of the content of the matrix resin and the organic cross-linked hollow particles.

[0078] In addition, in 3D printing modeling, as the nozzle that discharges the 3D printing modeling material moves, the 3D printing modeling material continuously produces fine fibers, so-called wire drawing. The 3D printing modeling material formed by using a 3D printing modeling resin mixture with a small content of organic cross-linked hollow particles has a tendency to be less likely to produce such wire drawing. Therefore, when it is necessary to suppress the generation of wire drawing, the content of the organic cross-linked hollow particles is preferably 50 parts by weight or less, more preferably 40 parts by weight or less, and further preferably 35 parts by weight or less relative to the total of 100 parts by weight of the content of the base resin and the organic cross-linked hollow particles.

[0079] [Method for producing organic crosslinked hollow particles]

[0080] The organic crosslinked hollow particles used in the present invention can be preferably produced by a production method comprising the following (A) mixed solution preparation step, (B) suspension step, (C) polymerization step, and (D) solvent removal step.

[0081] That is, the organic crosslinked hollow particles used in the present invention can be preferably produced by a production method including the following steps:

[0082] (A) a mixed solution preparation step of preparing a mixed solution containing a polymerizable monomer including a cross-linkable monomer, a hydrophobic organic solvent, a polymerization initiator, and an aqueous medium;

[0083] (B) a suspension step of suspending the mixed solution obtained in the mixed solution preparation step to prepare a suspension in which droplets of a polymerizable monomer composition containing a polymerizable monomer, a hydrophobic organic solvent and a polymerization initiator are dispersed in an aqueous medium;

[0084] (C) a polymerization step of subjecting the suspension obtained in the suspending step to a polymerization reaction to prepare a precursor composition including precursor particles having a hollow portion and enclosing a hydrophobic organic solvent in the hollow portion; and

[0085] (D) A solvent removal step of removing the hydrophobic organic solvent contained in the precursor particles obtained in the polymerization step.

[0086] (A) Mixed solution preparation process

[0087] The mixed solution preparation step is a step of preparing a mixed solution containing a polymerizable monomer including a crosslinkable monomer, a hydrophobic organic solvent, a polymerization initiator, and an aqueous medium. The organic crosslinked hollow particles used in the present invention are preferably produced by a production method including such steps.

[0088] (Polymerizable Monomer)

[0089] As the polymerizable monomer, the above-mentioned crosslinkable monomer and, if necessary, the above-mentioned monofunctional monomer are used. The monomer composition of the polymerizable monomer may be any monomer composition as long as the monomer composition of the target shell polymer can be obtained.

[0090] The content of the polymerizable monomer (the total amount of the cross-linking monomer and the monofunctional monomer) in the mixed solution prepared in the mixed solution preparation step is not particularly limited, but is preferably 15 to 55% by mass, and more preferably 25 to 50% by mass, relative to 100% by mass of the total mass of the components in the mixed solution excluding the aqueous medium.

[0091] (Hydrophobic organic solvent)

[0092] As the hydrophobic organic solvent, a non-polymerizable and poorly water-soluble organic solvent is used. The hydrophobic organic solvent functions as a spacer that forms a hollow portion inside the particle.

[0093] There are no particular limitations on the hydrophobic organic solvent, and hydrocarbon solvents can be preferably used. Specific examples thereof include: saturated hydrocarbon solvents such as butane, pentane, n-hexane, cyclohexane, heptane, octane, etc.; aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.; and highly volatile solvents such as carbon disulfide and carbon tetrachloride.

[0094] The content of the hydrophobic organic solvent in the mixed solution is preferably 50 to 500 parts by mass, more preferably 60 to 400 parts by mass, further preferably 80 to 350 parts by mass, particularly preferably 100 to 300 parts by mass, based on 100 parts by mass of the total mass of the polymerizable monomers.

[0095] (Polymerization initiator)

[0096] As the polymerization initiator, an oil-soluble polymerization initiator is preferably used. By using an oil-soluble polymerization initiator as the polymerization initiator, the polymerization initiator can be appropriately introduced into the liquid droplets of the polymerizable monomer composition in the suspension obtained in the suspension step described later.

[0097] The oil-soluble polymerization initiator is not particularly limited as long as it is a lipophilic polymerization initiator having a solubility in water of 0.2 mass % or less. Examples of the oil-soluble polymerization initiator include benzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-diethylhexanoate, tert-butyl peroxypivalate, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobisisobutyronitrile.

[0098] The content of the polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, and further preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the total mass of the polymerizable monomers in the mixed solution. By making the content of the polymerization initiator within the above range, the polymerization reaction can be fully carried out, and the possibility of residual polymerization initiator after the polymerization reaction is completed is small, and the possibility of unexpected side reactions is also small.

[0099] (Water-based media)

[0100] Examples of the aqueous medium include a medium selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent.

[0101] The hydrophilic solvent is not particularly limited as long as it is sufficiently miscible with water without phase separation, and examples thereof include alcohols such as methanol and ethanol; tetrahydrofuran (THF); and dimethyl sulfoxide (DMSO).

[0102] Among aqueous media, water is preferably used from the perspective of its polarity. When a mixture of water and a hydrophilic solvent is used, it is preferred that the polarity of the mixture as a whole does not become too low from the perspective of appropriately forming droplets of a polymerizable monomer composition containing a polymerizable monomer, a hydrophobic organic solvent, and a polymerization initiator. When a mixture of water and a hydrophilic solvent is used, it is preferred that the mixing ratio (mass ratio) of water to the hydrophilic solvent is water:hydrophilic solvent = 99:1 to 50:50.

[0103] In addition, in the mixed solution preparation step, it is preferred to use a dispersion stabilizer in addition to the polymerizable monomer, the hydrophobic organic solvent, the polymerization initiator and the aqueous medium. That is, the mixed solution preparation step is preferably a step of preparing a mixed solution containing the polymerizable monomer, the hydrophobic organic solvent, the polymerization initiator, the aqueous medium and the dispersion stabilizer.

[0104] The dispersion stabilizer is a compound that disperses the droplets of the polymerizable monomer composition in the aqueous medium in the suspension step described below, and may be either an inorganic dispersion stabilizer or an organic dispersion stabilizer.

[0105] Examples of the inorganic dispersion stabilizer include colloidal silica, magnesium hydroxide, calcium phosphate, calcium carbonate, barium sulfate, calcium oxalate, calcium carbonate, magnesium carbonate, barium carbonate, tricalcium phosphate, aluminum hydroxide, magnesium hydroxide, iron hydroxide, hydroxyapatite, diatomaceous earth silicate, clay, and bentonite.

[0106] Examples of the organic dispersion stabilizer include methyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and starch.

[0107] Among these, inorganic dispersion stabilizers are preferred from the viewpoint of high dispersion stabilization effect and easier control of the particle size of droplets of a polymerizable monomer composition containing a polymerizable monomer, a hydrophobic organic solvent and a polymerization initiator. Among inorganic dispersion stabilizers, metal-containing dispersion stabilizers are preferred, and water-sparsely soluble inorganic metal salts are more preferred. In addition, as water-sparsely soluble inorganic metal salts, inorganic metal salts having a solubility of 0.5 g or less in 100 g of water are preferred, and examples thereof include magnesium hydroxide, calcium hydroxide, barium hydroxide, calcium phosphate, etc., and magnesium hydroxide is more preferred among these. Dispersion stabilizers can be used alone or in combination of two or more.

[0108] In addition, from the viewpoint of further improving the dispersion stabilization effect, the dispersion stabilizer is preferably used in the state of a dispersion liquid or solution of the dispersion stabilizer by dispersing or dissolving it in an aqueous medium. That is, in the mixed solution preparation process, the mixed solution is preferably obtained by mixing the dispersion stabilizer in the state of a dispersion liquid or solution with a polymerizable monomer, a hydrophobic organic solvent and a polymerization initiator. In addition, as the aqueous medium, the above-mentioned aqueous medium can be used.

[0109] The mixing ratio of the dispersion stabilizer and the aqueous medium in the dispersion or solution of the dispersion stabilizer is preferably 0.7:100 to 7:100, more preferably 1.0:100 to 4.0:100, and further preferably 1.4:100 to 3:100, in terms of the mass ratio of "dispersion stabilizer: aqueous medium". By setting the mixing ratio of the dispersion stabilizer and the aqueous medium within the above range, the dispersion stabilization effect can be more appropriately improved.

[0110] As a method for preparing a dispersion or solution of a dispersion stabilizer, a method of directly mixing the dispersion stabilizer with an aqueous medium can be adopted, but a method of generating the dispersion stabilizer by mixing two or more compounds serving as precursors of the dispersion stabilizer (i.e., two or more precursor compounds) in an aqueous medium and reacting them is preferred.

[0111] In addition, the precursor compound used when mixing two or more precursor compounds in an aqueous medium is not particularly limited. For example, when using a water-insoluble hydroxide salt such as magnesium hydroxide, calcium hydroxide, or barium hydroxide as a dispersion stabilizer, the two or more precursor compounds include a combination of a water-soluble polyvalent metal salt and an alkali metal hydroxide.

[0112] As water-soluble polyvalent metal salts, hydrochlorides, sulfates, nitrates, acetates, etc. of polyvalent metals such as magnesium, calcium, aluminum, iron, copper, manganese, nickel, tin, etc. can be enumerated. Among these, water-soluble salts of magnesium and calcium are preferred. In addition, as alkali metal hydroxides, sodium hydroxide, potassium hydroxide, lithium hydroxide, etc. can be enumerated. For example, when magnesium hydroxide is used as a dispersion stabilizer, as two or more precursor compounds, a combination of magnesium chloride and sodium hydroxide is preferred.

[0113] The method for mixing two or more precursor compounds in an aqueous medium is not particularly limited. In the case of a combination of a water-soluble polyvalent metal salt and an alkali metal hydroxide, a method of dropping an aqueous medium solution of an alkali metal hydroxide into an aqueous medium solution of a water-soluble polyvalent metal salt under stirring is preferred.

[0114] The content of the water-soluble polyvalent metal salt in the aqueous medium solution of the water-soluble polyvalent metal salt is preferably 2 to 8 parts by weight, more preferably 3 to 6 parts by weight, relative to 100 parts by weight of the aqueous medium solution. In addition, the content of the alkali metal hydroxide in the aqueous medium solution of the alkali metal hydroxide is preferably 6 to 20 parts by weight, more preferably 8 to 18 parts by weight, relative to 100 parts by weight of the aqueous medium solution. In addition, as the aqueous medium, the above-mentioned aqueous medium can be used.

[0115] In the mixed solution preparation process, the above-mentioned components are mixed by stirring, etc., so that a mixed solution can be obtained. At this time, in addition to the above-mentioned components, other materials can be mixed as needed. In the mixed solution preparation process, a mixed solution is prepared in which an oil phase containing lipophilic materials such as a polymerizable monomer, a hydrophobic organic solvent and a polymerization initiator is dispersed in a water phase containing an aqueous medium and a dispersion stabilizer used as needed with a particle size of several millimeters. The dispersion state of these components in the mixed solution can also be observed with the naked eye according to the type of each component.

[0116] Furthermore, in the mixed liquid preparation step, from the viewpoint of making the composition of the shell portion more uniform, it is preferred to prepare in advance an oil phase containing a polymerizable monomer, a hydrophobic organic solvent and a polymerization initiator, and to mix the oil phase with a dispersion or solution in which a dispersion stabilizer is dispersed or dissolved in an aqueous medium, thereby preparing the mixed liquid.

[0117] (B) Suspension process

[0118] The suspending step is a step of preparing a suspension in which droplets of a polymerizable monomer composition containing a polymerizable monomer, a hydrophobic organic solvent and a polymerization initiator are dispersed in an aqueous medium by suspending the mixed solution obtained in the mixed solution preparing step.

[0119] The method for suspending droplets of the polymerizable monomer composition is not particularly limited, but a method in which the mixed solution obtained in the mixed solution preparation step is stirred using a stirring device capable of strong stirring is preferred.

[0120] In the suspension step, a suspension in which droplets of the polymerizable monomer composition containing the above-mentioned lipophilic material are uniformly dispersed in an aqueous medium can be obtained as a suspension. Such droplets of the polymerizable monomer composition are difficult to observe with the naked eye, but can be observed by a known observation device such as an optical microscope. In addition, in the suspension step, since phase separation occurs in the droplets of the polymerizable monomer composition, the hydrophobic organic solvent with low polarity tends to concentrate inside the droplets. As a result, in the obtained droplets, the hydrophobic organic solvent is distributed inside, and materials other than the hydrophobic organic solvent are distributed at the edges.

[0121] (C) Polymerization process

[0122] The polymerization step is a step of subjecting the suspension prepared in the above-mentioned suspending step to a polymerization reaction to prepare a precursor composition having a hollow portion and enclosing a hydrophobic organic solvent in the hollow portion.

[0123] In the polymerization step, the polymerizable monomer in the polymerizable monomer composition droplets is polymerized in a state where the hydrophobic organic solvent is enclosed in the droplets, thereby forming precursor particles having a shell of a resin containing a polymer of the polymerizable monomer and a hollow portion filled with the hydrophobic organic solvent.

[0124] In the polymerization process, by supplying the droplets of the polymerizable monomer composition to the polymerization reaction in a state in which the hydrophobic organic solvent is contained, the polymerization reaction can be easily carried out while maintaining the shape, and the size and porosity of the precursor particles can be easily adjusted. In addition, since the polymerizable monomer and the hydrophobic organic solvent are used in combination, the polarity of the hydrophobic organic solvent is low relative to the shell of the precursor particle, and the hydrophobic organic solvent is not easy to merge with the shell, so phase separation will occur sufficiently, and the hollow part is likely to be only one.

[0125] The polymerization method is not particularly limited, and examples thereof include batch method (intermittent method), semi-continuous method, continuous method, etc. The polymerization temperature is preferably 40 to 90° C., more preferably 50 to 80° C. The polymerization reaction time is preferably 1 to 48 hours, more preferably 3 to 24 hours.

[0126] Through the polymerization step, a precursor composition can be obtained in which the precursor particles enclosing the hydrophobic solvent are dispersed in the aqueous phase containing the aqueous medium as a main component.

[0127] (D) Solvent Removal Step

[0128] The solvent removal step is a step of removing the hydrophobic organic solvent contained in the precursor particles obtained in the polymerization step.

[0129] Preferably, before removing the solvent by the solvent removal step, the precursor composition obtained by the polymerization step is preliminarily subjected to solid-liquid separation, and a solid component containing precursor particles containing a hydrophobic organic solvent is obtained by solid-liquid separation. After obtaining the solid component containing the precursor particles by solid-liquid separation, the hydrophobic organic solvent contained in the precursor particles is removed in the gas, whereby the hydrophobic organic solvent inside the precursor particles is replaced with air, and organic crosslinked hollow particles filled with gas can be obtained.

[0130] The method of solid-liquid separation of the precursor composition is not particularly limited, and known methods can be used. As the method of solid-liquid separation, for example, centrifugation, filtration, static separation, etc. can be mentioned. Among these, centrifugation or filtration can be used. From the viewpoint of simplicity of operation, centrifugation can be used. After solid-liquid separation, any process such as pre-drying process can also be further used. As the pre-drying process, for example, the solid component obtained after the solid-liquid separation process can be mentioned by drying appliances such as drying devices such as drying machines, hand dryers, etc. to carry out pre-drying.

[0131] In addition, strictly speaking, the "gas" in the solvent removal process refers to the environment in which there is no liquid component at all outside the precursor particles and the environment in which there is only a trace amount of liquid component that does not affect the removal of the hydrophobic organic solvent outside the precursor particles. "Gas" can be changed to be expressed as a state in which the precursor particles are not present in the slurry, and can also be changed to be expressed as a state in which the precursor particles are present in the dry powder. That is, in the solvent removal process, it is desired to remove the hydrophobic organic solvent under the environment in which the precursor particles are directly in contact with the gas outside.

[0132] The method for removing the hydrophobic organic solvent in the precursor particles in the gas is not particularly limited, and a known method can be used, such as reduced pressure drying method, heating drying method, airflow drying method, and these methods can also be used in combination. In particular, when using the heating drying method, the heating temperature needs to be above the boiling point of the hydrophobic organic solvent and below the maximum temperature at which the shell structure of the precursor particles will not be broken. Therefore, although it depends on the composition of the shell in the precursor particles and the type of the hydrophobic organic solvent, the heating temperature is preferably 50 to 200 ° C, more preferably 70 to 200 ° C, and further preferably 100 to 200 ° C. By the drying operation in the gas, the hydrophobic organic solvent inside the precursor particles is replaced by the external gas, and as a result, organic crosslinked hollow particles in which the gas occupies the hollow portion can be obtained.

[0133] The drying atmosphere is not particularly limited and can be appropriately selected according to the purpose of the organic crosslinked hollow particles. As the drying atmosphere, for example, air, oxygen, nitrogen, argon, etc. can be considered. In addition, after the interior of the organic crosslinked hollow particles is temporarily filled with gas, reduced pressure drying is performed, thereby the organic crosslinked hollow particles whose interior is temporarily vacuum can also be obtained.

[0134] Alternatively, instead of performing solid-liquid separation of the slurry-like precursor composition obtained in the polymerization step, the hydrophobic organic solvent contained in the precursor particles may be replaced with the aqueous medium of the slurry in the slurry containing the precursor particles and the aqueous medium to remove the hydrophobic organic solvent.

[0135] When comparing the method of "after solid-liquid separation of a slurry-like precursor composition, removing the hydrophobic organic solvent in the precursor particles in a gas, thereby obtaining organic crosslinked hollow particles whose hollow parts are filled with gas" with the method of "in a slurry comprising precursor particles and an aqueous medium, replacing the hydrophobic organic solvent contained in the precursor particles with the aqueous medium of the slurry, performing solid-liquid separation, and removing the aqueous medium in the precursor particles in a gas, thereby obtaining organic crosslinked hollow particles whose hollow parts are filled with gas", the former method has the advantage that the organic crosslinked hollow particles are not easily broken in the step of removing the hydrophobic organic solvent, and the latter method has the advantage that the residual hydrophobic organic solvent is reduced by blowing with an inert gas.

[0136] In addition, as a method for removing the hydrophobic organic solvent contained in the precursor particles without performing solid-liquid separation on the slurry-like precursor composition obtained in the polymerization step after the polymerization step and before the solid-liquid separation step, for example, the following methods can be used: a method of distilling off the hydrophobic organic solvent contained in the precursor particles from the precursor composition under a specified pressure (under high pressure, under normal pressure, or under reduced pressure); a method of introducing an inert gas such as nitrogen, argon, helium, or water vapor into the precursor composition under a specified pressure (under high pressure, under normal pressure, or under reduced pressure) and distilling it off.

[0137] (E) Other processes

[0138] The above-mentioned production method may include other steps. Examples of other steps include (E-1) a cleaning step and (E-2) a hollow portion re-replacement step.

[0139] (E-1) Cleaning process

[0140] The above-mentioned manufacture method preferably comprises a cleaning process before or after the recovery process. For example, when using a dispersion stabilizer, in order to remove the residual dispersion stabilizer in the organic crosslinked hollow particle slurry comprising organic crosslinked hollow particles and an aqueous medium before the recovery process, it is preferably included in a cleaning process of adding an acid or alkali to clean. When the dispersion stabilizer used is a dispersion stabilizer soluble in acid, it is preferably added to a precursor composition comprising precursor particles to clean, and on the other hand, when the dispersion stabilizer used is a dispersion stabilizer soluble in alkali, it is preferably added to a precursor composition comprising precursor particles to clean.

[0141] When an acid-soluble dispersion stabilizer is used as the dispersion stabilizer, an acid is added to the precursor composition containing the precursor particles to adjust the pH to preferably 6.5 or less, and more preferably to 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, and sulfuric acid is particularly preferred from the viewpoint of high removal efficiency of the dispersion stabilizer and small burden on the production equipment.

[0142] (E-2) Hollow portion replacement step

[0143] The re-replacement process of the hollow part refers to a process of replacing the gas or liquid inside the organic cross-linked hollow particles with other gas or liquid. By such replacement, the environment inside the organic cross-linked hollow particles can be changed, or molecules can be selectively enclosed inside the organic cross-linked hollow particles, or the chemical structure inside the organic cross-linked hollow particles can be modified according to the application.

[0144] [Other matching materials]

[0145] The resin mixture for 3D printing modeling of the present invention may be formed only by a matrix resin and organic cross-linked hollow particles, and may also contain other compounding materials other than these within the scope that does not impair the purpose of the present invention. In addition, the resin mixture for 3D printing modeling of the present invention preferably does not substantially contain hollow particles other than organic cross-linked hollow particles (the content of hollow particles other than organic cross-linked hollow particles is preferably less than 1% by weight).

[0146] As other compounding materials, it can contain: fillers including organic fillers and inorganic fillers, colorants including dyes and pigments, antistatic agents, end-capping agents, ultraviolet absorbers, anti-ultraviolet agents, heat stabilizers, light stabilizers, anti-condensation agents, anti-fogging agents, plasticizers, flame retardants, anti-coloring agents, anti-colloid agents, antioxidants, mold release agents (erucic acid amide, stearic acid amide, oleic acid amide, vinyl bisstearic acid amide, vinyl bisoleic acid amide, vinyl bislauric acid amide), moisture-proof agents, oxygen barriers, crystal nucleating agents, compatibilizers and other additives. The above compounding materials can be used alone or in combination of two or more.

[0147] Examples of the organic filler include fibrous organic fillers such as aramid fiber, polyimide fiber, polybenzothiazole fiber, and polyethylene fiber; and plant fibers such as hemp and bamboo.

[0148] Examples of the inorganic filler include glass beads, glass fibers, flat cross-section glass fibers, glass milled fibers, ceramic beads, wollastonite, mica, synthetic mica, sericite, talc, clay, zeolite, bentonite, kaolin, dolomite, silica, zeolite, feldspar powder, potassium titanate, finely powdered silicic acid, calcium carbonate, magnesium carbonate, barium sulfate, aluminum oxide, magnesium oxide, calcium oxide, titanium oxide, silicon oxide, aluminum silicate, zirconium silicate, gypsum, homogeneous quartzite, dawsonite, montmorillonite, calcium sulfide, zinc oxide, boron nitride, glass flakes, metal flakes, metal fibers, basalt fibers, asbestos, ceramic fibers, slag potassium titanate, boron whiskers, aluminum borate, xonotlite, palygorskite, and sepiolite. Examples of the inorganic filler include carbon-based fillers such as carbon fibers, carbon milled fibers, and carbon nanotubes; carbon black; graphite; and carbon flakes.

[0149] In addition, the organic filler and the inorganic filler are preferably not in the form of hollow particles, and specifically, are preferably in the form of fibers, particles, or plates.

[0150] The content of other compounding materials in the resin mixture for 3D printing modeling is not particularly limited as long as it is within the range that does not impair the purpose of the present invention. It is preferably 0 to 30 parts by weight, more preferably 0 to 10 parts by weight, and further preferably 0 to 5 parts by weight relative to 100 parts by weight of the total content of the matrix resin and the organic cross-linked hollow particles.

[0151] [Method for producing resin mixture for 3D printing]

[0152] The resin mixture for 3D printing modeling is obtained by mixing the above-mentioned base resin and organic cross-linked hollow particles with the matching materials used as needed. Specifically, it is preferred to add the organic cross-linked hollow particles used in the present invention and the matching materials used as needed to the molten base resin, and melt-mix, thereby mixing. In this case, all the components can be independently supplied to the melt mixer, on the other hand, after a part of the components are pre-mixed, the pre-mixed components and the remaining components can be independently supplied to the melt mixer.

[0153] The mixing of matrix resin, organic cross-linked hollow particles and the compounding materials used as needed can be carried out using, for example, a kneader, a roll mill, a Brabender mixer, a single-shaft extruder, a double-shaft extruder, a multi-shaft extruder, etc. Among them, it is preferred to use an extruder such as a single-shaft extruder, a double-shaft extruder, a multi-shaft extruder for melt mixing, and from the aspect of obtaining a 3D printing modeling resin mixture with excellent uniformity with high production efficiency, it is preferred to use a double-shaft extruder for melt mixing. In the case of using an extruder for melt mixing, the cylinder temperature (double-shaft mixing temperature) is preferably 150 to 220°C, more preferably 170 to 210°C, and the mold temperature (extrusion molding temperature) is preferably 160 to 220°C, more preferably 180 to 210°C.

[0154] <Materials for 3D printing>

[0155] According to the present invention, a 3D printing modeling material formed by the above-mentioned 3D printing modeling resin mixture of the present invention is provided. The 3D printing modeling material of the present invention has excellent modeling properties and can form a modeling object with excellent reproducibility of the modeling model with sufficient strength. In addition, the 3D printing modeling material of the present invention can form a lightweight modeling object with an apparent density lower than the density of the matrix resin.

[0156] The 3D printing modeling material of the present invention is a material obtained by molding the above-mentioned 3D printing modeling resin mixture of the present invention into a shape that can be applied to a 3D printer. Examples of shapes that can be applied to a 3D printer include granular shapes, filamentary shapes, and the like. From the perspective of being applicable to a general fused deposition modeling 3D printer, the 3D printing modeling material of the present invention can also be in the form of filaments.

[0157] The apparent density of the 3D printing modeling material of the present invention is preferably 0.4 to 0.99 times, more preferably 0.45 to 0.98 times, and further preferably 0.5 to 0.95 times the density of the base resin constituting the 3D printing modeling material of the present invention. According to the present invention, the 3D printing modeling material can have excellent modeling properties and be lightweight as described above (that is, the apparent density of the 3D printing modeling material is lower than the density of the base resin as described above), and as a result, the obtained modeling object can also be lightweight. In addition, the method for measuring the apparent density of the 3D printing modeling material can be measured by the same method as the method for measuring the apparent density of organic cross-linked hollow particles.

[0158] (Method for manufacturing materials for 3D printing modeling)

[0159] The 3D printing modeling material of the present invention can be obtained by molding the 3D printing modeling resin mixture of the present invention into a desired shape by a known molding method such as extrusion molding, injection molding, press molding, compression molding, etc. Among them, extrusion molding is preferred from the viewpoint of being able to manufacture filamentous and granular 3D printing modeling materials that can be applied to general 3D printers with high production efficiency.

[0160] In addition, when an extruder such as a twin-shaft extruder is used to manufacture a resin mixture for 3D printing as described above, the kneaded resin mixture for 3D printing is extruded from the extruder and continuously molded into granules, filaments, etc., thereby making it possible to manufacture granules, filaments, etc., 3D printing materials with high production efficiency. In this case, the preferred cylinder temperature and mold temperature are as described above.

[0161] The particles can be obtained by, for example, extruding the above-mentioned 3D printing resin mixture of the present invention and directly cutting it into particles. On the other hand, it can also be obtained by extruding the above-mentioned 3D printing resin mixture of the present invention in a strand shape and then cutting it after cooling. The particles can also be directly used as a granular 3D printing material. On the other hand, the particles can also be used to obtain a 3D printing material having a desired shape such as a filament.

[0162] The filamentary 3D printing modeling material may be a monofilament or a multifilament, preferably a monofilament. In addition, the filamentary 3D printing modeling material may be an unstretched material or a stretched material. The diameter of the filamentary 3D printing modeling material can be freely adjusted in a manner suitable for the 3D printer to be used, and is generally preferably 1.5 to 3.2 mm, and more preferably 1.6 to 3.1 mm.

[0163] The filamentous 3D printing material can be produced by, for example, extruding a 3D printing resin mixture into a filamentous shape and then cooling and solidifying it. The cooling and solidification is usually performed at 0 to 100°C, preferably in a liquid bath at 20 to 80°C.

[0164] After the resin mixture for 3D printing is extruded into a filament, the extruded product can also be stretched before or after it is cooled and solidified. As a stretching method, for example, the following method can be cited: while performing heat treatment at 170 to 250°C, stretching at a stretching ratio of 2 to 5 times, repeating such stretching as needed, but not limited to such a method. After stretching, it is preferred to perform a relaxation heat treatment (stretching ratio of 0.9 to 0.99 times) while performing a heat treatment at 130 to 200°C.

[0165] The filamentous 3D printing modeling material obtained as described above is usually wound into a bobbin or the like and then stored in a box or the like.

[0166] (Uses of 3D printing materials)

[0167] The 3D printing modeling material of the present invention can be applied to 3D printers with a high degree of design freedom, and thus can be applied to a very wide range of uses. In particular, the 3D printing modeling material of the present invention has excellent modeling properties and can form lightweight models, and thus can be preferably applied to uses that require models with complex three-dimensional structures to be obtained with sufficient strength, uses that require lightweighting, and the like.

[0168] The use of the 3D printing modeling material of the present invention is not particularly limited, and examples thereof include: components of mobile bodies such as airplanes, cars, trains, motorcycles, ships, bicycles, drones, satellites, and shuttles (for example, space shuttles); components of daily necessities such as stationery, brushes, media, jewelry, watches, cooking utensils, kitchen supplies, cleaning utensils, home appliances, and toys; components of wearable devices such as shoes, clothing, zippers, buttons, snaps, gloves, shin guards, hats, knee pads, elbow pads, helmets, and headgear; components of devices worn on the body such as orthotics, auxiliary clothing, and wearable devices ; components of competitive sports equipment such as rackets and grips; various materials such as agricultural materials, gardening materials, fishery materials, civil engineering / construction materials; electrical / electronic components such as circuit boards and sleeves; industrial components such as gears, motors, tools, propellers, impellers, wheels, mechanical device housings, gaskets, O-rings, piping, connectors, reflectors, etc.; medical components such as medical equipment, stents, catheters, orthodontic appliances, artificial organs, etc.; containers such as food containers, portable terminal housings, bottles, etc.; scale models of cars, houses, buildings, etc.; thermal insulation materials; sound insulation materials; vibration reduction materials; cushioning materials, etc.

[0169] Among them, most of the components of mobile bodies such as drones have complex three-dimensional shapes, so most of them are also modeled by 3D printing. Here, in the components of mobile bodies such as drones, in addition to the need to obtain components with complex three-dimensional structures with sufficient strength, the requirements for lightweight components are extremely high. Therefore, the 3D printing modeling material of the present invention can be preferably used for component uses of mobile bodies such as drones. More specifically, the 3D printing modeling material of the present invention can be preferably used for: components such as the main body, propellers, arms, and feet of mobile bodies such as drones; various component uses such as housings, protective components, reinforcing components, supports, and vibration-proof components for protecting or supporting components such as motors, batteries, cameras, propellers, and antennas possessed by mobile bodies.

[0170] <Modelling>

[0171] The object of the present invention can be obtained by 3D printing using the 3D printing material of the present invention.

[0172] The modeled object of the present invention is obtained by using the 3D printing modeling material of the present invention, and therefore has a three-dimensional shape with excellent reproducibility of the modeling model, has sufficient strength, and is lightweight. The modeled object of the present invention can be obtained by the modeling method of the present invention described below.

[0173] <Modeling method>

[0174] According to the present invention, a modeling method for 3D printing modeling using the above-mentioned 3D printing modeling material of the present invention is provided. According to the modeling method of the present invention, the above-mentioned modeling object of the present invention can be obtained.

[0175] As the method of 3D printing modeling, there can be cited a fused deposition modeling method (FDM method), a powder sintering method, an inkjet method, a light modeling method (SLA method), etc. Among these, the 3D printing modeling material of the present invention can be preferably applied to 3D printing modeling of the fused deposition modeling method. That is, the modeling method of the present invention is preferably a method for performing 3D printing modeling of the fused deposition modeling method, and further, the modeling object of the present invention is preferably obtained by 3D printing modeling of the fused deposition modeling method.

[0176] Hereinafter, a case where a fused deposition modeling method is adopted will be described, but the modeling method of the present invention is not limited to such a case.

[0177] First, the 3D printing material of the present invention is supplied to a 3D printer. When using filaments (filamentous 3D printing material), the filaments are usually engaged with a driving roller such as a clamping roller or a gear roller, and are supplied to an extruder head while being pulled.

[0178] The 3D printing modeling material supplied to the 3D printer is heated and melted by the extrusion head and extruded from the front nozzle. The temperature of the extrusion head (nozzle temperature) is preferably 150-220°C, more preferably 170-210°C. The temperature of the 3D printing modeling material discharged from the extrusion head is preferably 160-220°C, more preferably 180-210°C. In addition, the base temperature is preferably below 80°C. By making the temperature of the 3D printing modeling material discharged from the extrusion head within the above range, a lightweight modeling object can be modeled with excellent productivity and better modeling properties. In addition, by making the above temperature within the above range, it is easy to prevent the occurrence of undesirable conditions such as thermal decomposition, burning, yellowing, smoking, odor, stickiness, and poor appearance of the resin.

[0179] The 3D printing material discharged from the extruder is preferably discharged in a strand shape with a diameter of 0.01 to 1.0 mm, more preferably 0.02 to 0.5 mm. If the 3D printing material is discharged in such a shape, the reproducibility of the modeling model tends to be better, so it is preferred.

[0180] The modeled object of the present invention and the modeling method of the present invention can be preferably applied to the above-mentioned uses as the use of the 3D printing modeling material of the present invention.

[0181] In addition, when using 3D printing material for fused deposition modeling, when the strands of 3D printing material discharged from the extruder are stacked while making a modeled object, the adhesion between the strands of 3D printing material discharged first and the strands of 3D printing material discharged above is sometimes insufficient, resulting in insufficient strength of the obtained modeled object. When using 3D printing material containing, for example, an inorganic component as a main component, the above-mentioned adhesion is likely to be insufficient, resulting in insufficient strength of the obtained modeled object.

[0182] In addition, in the 3D printing modeling material formed by a mixture of a matrix resin and thermoplastic hollow particles, it is difficult to maintain the hollow shape from the hollow particles when manufacturing the 3D printing modeling material or performing 3D printing modeling using the 3D printing modeling material, and the lightweight effect brought by the hollow particles is likely to become insufficient.

[0183] In contrast, the 3D printing modeling material formed by the 3D printing modeling resin mixture of the present invention has good adhesion to each other and is easy to maintain the hollow shape from the hollow particles, so it has excellent modeling properties and can form a lightweight modeling object. Therefore, according to the present invention, a lightweight modeling object can be formed with excellent modeling properties.

[0184] Example

[0185] The present invention is further specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts and % are by mass unless otherwise specified. Various measurements are performed according to the following methods.

[0186] <Apparent density>

[0187] The capacity is 100cm 3 Fill the volumetric flask to about 30 cm 3 The sample was accurately weighed. Next, the volumetric flask filled with the sample was accurately filled with isopropanol to the scale line while being careful not to mix in bubbles. The mass of isopropanol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm2) of the sample was calculated based on the following formula (II): 3 ). In addition, when the sample size is large, other instruments are used instead of the volumetric flask with a capacity of 100 cm3 to measure the apparent density.

[0188] The apparent density of the sample D1 (g / cm 3 ) = [mass of sample] ÷ (100 - [mass of isopropanol] ÷ [density of isopropanol at the measurement temperature]) (II)

[0189] <Styling>

[0190] In each of the examples and comparative examples, the modeling properties when 3D printing modeling was performed using the "3D Benchy" as a modeling model were evaluated according to the following criteria.

[0191] A: A shaped object with a beautiful appearance and sufficient strength and excellent reproducibility of the shaped model was obtained.

[0192] B: A molded object with sufficient strength and excellent reproducibility of the molded model was obtained, but some wire drawing was observed due to the movement of the nozzle during 3D printing.

[0193] C: When the object is removed from the 3D printer after 3D printing, the object is broken into multiple components due to the tiny stress during the measurement of the apparent density.

[0194] <Bending test>

[0195] Using the bending test samples obtained in each of the Examples and Comparative Examples, bending tests were performed according to the following procedures (1) to (3).

[0196] (1) Bending strength

[0197] The bending strength (bending stress calculated based on the maximum load until fracture) of the bending test sample was measured in accordance with JIS K7171.

[0198] (2) Deformation

[0199] The bending test sample was bent at a test speed of 2 mm / min using the same bending test machine as that used for the determination of bending strength. After the bending test sample reached a deflection of 4 mm (i.e., 2 minutes after the start of bending), the deflection was maintained at 4 mm for 5 minutes. Next, the bending stress was unloaded, and the deformation of the bending test sample after unloading (the amount of deflection remaining in the bending test sample) was measured.

[0200] (3) Evaluation of bending test results

[0201] The bending test results were evaluated according to the following criteria based on the bending strength measured in (1) and the deformation measured in (2) above.

[0202] A: The bending strength measured in (1) is 20 MPa or more and the deformation measured in (2) is less than 1 mm.

[0203] B: The bending strength measured in (1) is 5 MPa or more and less than 20 MPa and the deformation measured in (2) is less than 1 mm.

[0204] C: The bending strength measured in (1) is 5 MPa or more and less than 20 MPa and the deformation measured in (2) is 1 mm or more and less than 3 mm.

[0205] D: The bending strength measured in (1) is less than 5 MPa, or the deformation measured in (2) is 3 mm or more, or the bending test sample is broken during the measurement of the deformation in (2), and the deformation cannot be measured.

[0206] [Production Example 1 (Production Example of Organic Crosslinked Hollow Particles 1)]

[0207] (1) Mixed solution preparation process

[0208] First, the following materials were mixed to prepare an oil phase.

[0209] Ethylene glycol dimethacrylate: 31.85 parts (difunctional heteroatom-containing crosslinking monomer);

[0210] Pentaerythritol tetraacrylate (tetrafunctional heteroatom-containing crosslinking monomer): 9.1 parts;

[0211] Divinylbenzene (difunctional crosslinking hydrocarbon monomer): 4.37 parts;

[0212] Ethylvinylbenzene (monofunctional hydrocarbon monomer): 0.182 parts;

[0213] 2,2'-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator): 1.04 parts;

[0214] Hexane: 54.5 parts.

[0215] Next, in a stirring tank, an aqueous solution of 16.5 parts of sodium hydroxide (alkali metal hydroxide) dissolved in 55 parts of ion exchange water was slowly added to an aqueous solution of 23.5 parts of magnesium chloride (water-soluble multivalent metal salt) dissolved in 225 parts of ion exchange water under stirring to prepare a magnesium hydroxide colloid (water-insoluble metal hydroxide colloid) dispersion to obtain an aqueous phase. A mixed solution was prepared by mixing the obtained aqueous phase with an oil phase.

[0216] (2) Suspension process

[0217] Next, the mixed solution obtained in the mixed solution preparation step was suspended by stirring at 4000 rpm for 1 minute using a disperser (manufactured by Plemicus, product name: HOMOMIXER) to prepare a suspension in which monomer droplets containing a hydrophobic organic solvent were dispersed in water.

[0218] (3) Polymerization process

[0219] The suspension obtained in the above suspension step was heated to 65° C. in a nitrogen atmosphere and stirred for 24 hours at 65° C. to perform polymerization reaction. The polymerization reaction obtained a slurry of precursor particles containing a hydrophobic organic solvent dispersed in water, that is, a precursor composition.

[0220] (4) Cleaning process and solid-liquid separation process

[0221] The precursor composition obtained in the above polymerization step was washed with dilute sulfuric acid (25° C., 10 minutes) to a pH of 5.5 or less. Then, after separating the water by filtration, 200 parts of ion exchange water was newly added to re-slurry, and the water washing treatment (washing, filtration, dehydration) was repeated several times at room temperature (25° C.), and the solid content was obtained by filtration separation.

[0222] (5) Drying process

[0223] The precursor particles obtained in the solid-liquid separation step were heated for 24 hours in a vacuum dryer at 200°C to remove water and the internal solvent, thereby obtaining organic crosslinked hollow particles 1. The monomer composition of the shell polymer in the obtained organic crosslinked hollow particles 1 is substantially consistent with the composition of the polymerizable monomers supplied to the polymerization. The apparent density of the obtained organic crosslinked hollow particles 1 is 0.4 g / cm 3 .

[0224] [Production Example 2 (Production Example of Organic Crosslinked Hollow Particles 2)]

[0225] First, the following materials were mixed to prepare an oil phase.

[0226] Ethylene glycol dimethacrylate: 31.85 parts;

[0227] Pentaerythritol tetraacrylate (tetrafunctional heteroatom-containing crosslinking monomer): 9.1 parts;

[0228] Divinylbenzene (difunctional crosslinking hydrocarbon monomer): 4.37 parts;

[0229] Ethylvinylbenzene (monofunctional hydrocarbon monomer): 0.182 parts;

[0230] 2,2'-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator): 1.04 parts;

[0231] Hexane: 34.5 parts.

[0232] Then, the obtained oil phase was used, and except for this, the same method as in Preparation Example 1 was carried out to obtain organic crosslinked hollow particles 2. The monomer composition of the shell polymer in the obtained organic crosslinked hollow particles 2 was substantially the same as the composition of the polymerizable monomers supplied to the polymerization. The apparent density of the obtained organic crosslinked hollow particles 2 was 0.6 g / cm 3 .

[0233] The base resin and hollow particles used in each of the Examples and Comparative Examples are as follows.

[0234] [Base resin]

[0235] PLA resin: polylactic acid, density 1.25g / cm 3 ;

[0236] ABS resin: Acrylonitrile-butadiene-styrene resin, density 1.07g / cm 3 .

[0237] [Hollow particles]

[0238] Organic crosslinked hollow particles 1: hollow particles obtained in Preparation Example 1, with an apparent density of 0.4 g / cm 3 ;

[0239] Organic crosslinked hollow particles 2: hollow particles obtained in Preparation Example 2, with an apparent density of 0.6 g / cm 3 ;

[0240] Non-crosslinked organic hollow particles: Hollow particles having a shell and a hollow portion made of a styrene-acrylic acid copolymer (thermoplastic resin), trade name "TECHPOLYMER MBP-8", manufactured by Sekisui Chemicals Co., Ltd., apparent density 0.4 g / cm 3 ;

[0241] Inorganic hollow particles: volcanic ash hollow spheres, trade name "Winlight (registered trademark) SC-50", manufactured by Shira Fine Co., Ltd., apparent density 0.7 g / cm 3 .

[0242] [Example 1]

[0243] Using PLA resin (polylactic acid, density 1.25g / cm 3 ) is used as the matrix resin, and the organic crosslinked hollow particles 1 obtained in Manufacturing Example 1 are used as hollow particles. The matrix resin and the hollow particles are supplied to a twin-shaft kneading extruder in a ratio of 90 parts of the matrix resin to 10 parts of the hollow particles. Then, the twin-shaft kneading extrusion is carried out under the conditions of a twin-shaft kneading temperature of 190°C and an extrusion molding temperature of 200°C, thereby obtaining filaments (materials for 3D printing modeling). The apparent density of the obtained filaments is measured according to the above-mentioned measurement method. The results are shown in Table 1.

[0244] The obtained filaments were used to perform 3D printing under the following conditions to obtain a 3D Benchy-shaped object. The appearance of the obtained object is shown in Figure 1 In addition, the apparent density of the obtained shaped object was subjected to a bending test according to the above method. The results are shown in Table 1.

[0245] 3D printer: Fused deposition modeling 3D printer (trade name "da Vinci 1.0Pro", manufactured by XYZprinting Japan)

[0246] Nozzle temperature: 200℃

[0247] Modeling model: 3D Benchy (standard model for 3D printing modeling test)

[0248] In addition, the same conditions as above were used to obtain a bending test sample except that the model was changed to a bending test sample model (80 mm×10 mm×4 mm in height). The bending test was performed on the obtained bending test sample according to the above measurement method. The results are shown in Table 1.

[0249] [Examples 2 to 9 and Comparative Examples 1 to 2]

[0250] The types of matrix resin and hollow particles and their mixing ratios were changed as described in Table 1, and the same method as in Example 1 was used to obtain filaments (3D printing modeling materials). Then, using the obtained filaments, the same method as in Example 1 was used to obtain a 3D Benchy-shaped modeling object and a bending test sample. The obtained filaments, the modeling object, and the bending test sample were measured and tested in the same manner as in Example 1. The results are shown in Table 1.

[0251] In addition, when the object (3D Benchy) manufactured in Comparative Example 2 was removed from the 3D printer after 3D printing, the object was broken into multiple components due to the slight stress during the measurement of the apparent density, and its apparent density could not be measured.

[0252] [Table 1]

[0253]

[0254] As can be seen from Table 1, the 3D printing modeling resin mixture containing a matrix resin and organic cross-linked hollow particles can form a 3D printing modeling material, which has excellent modeling properties and can form lightweight modeling objects (Examples 1 to 9).

[0255] On the other hand, when non-crosslinked organic hollow particles were used as the hollow particles, a lightweight shaped object could not be obtained (Comparative Example 1).

[0256] Furthermore, when inorganic hollow particles were used as the hollow particles, the obtained 3D printing modeling material had poor modeling properties (Comparative Example 2).

Claims

1. A resin mixture for 3D printing, comprising a matrix resin and organic cross-linked hollow particles.

2. The resin mixture for 3D printing according to claim 1, wherein: The apparent density of the organic cross-linked hollow particles is 0.2 to 0.9 g / cm 3 .

3. The resin mixture for 3D printing according to claim 1 or 2, wherein: The content of the organic crosslinked hollow particles is 1 to 70 parts by weight relative to 100 parts by weight of the total content of the base resin and the organic crosslinked hollow particles.

4. The resin mixture for 3D printing according to any one of claims 1 to 3, wherein The organic crosslinked hollow particles have a shell formed of a shell polymer including a crosslinkable monomer unit.

5. The resin mixture for 3D printing according to any one of claims 1 to 4, wherein The shell polymer includes a heteroatom-containing crosslinkable monomer unit as the crosslinkable monomer unit. 6 . A 3D printing modeling material, which is formed from the 3D printing modeling resin mixture according to any one of claims 1 to 5.

7. The 3D printing modeling material according to claim 6, wherein: The 3D printing modeling material is used for 3D printing modeling by fused deposition modeling.

8. The 3D printing modeling material according to claim 6 or 7, wherein: The 3D printing modeling material is in the form of filaments. 9 . A modeled object obtained by 3D printing modeling using the 3D printing modeling material according to any one of claims 6 to 8 .

10. The sculpted object according to claim 9, wherein: The modeling object is obtained by 3D printing using a fused deposition modeling method.

11. A modeling method, using the 3D printing modeling material according to any one of claims 6 to 8 to perform 3D printing modeling.

12. The molding method according to claim 11, wherein: Perform 3D printing using fused deposition modeling.

Citation Information

Patent Citations

  • Method for manufacturing three-dimensional molded article, three-dimensional molded article, and composition for three-dimensional molding

    JP2016010914A